The differential expression of miRNAs between ovarian endometrioma and endometriosis-associated ovarian cancer - Natsuho Nakamura; Yoshito Terai; Misa Nunode; Kana Kokunai; Hiromi Konishi; Sayaka Taga; Mayumi Nakamura; Masae Yoo; Masami Hayashi; Yoshiki Yamashita; Masahide Ohmichi (BMC, 2020)
Abstract Background MicroRNAs (miRNAs) have been implicated to play a vital role in development, differentiation, cell proliferation and apoptosis. However, which miRNAs are actually associated with endometriosis-associated ovarian cancer remains controversial. Methods Serum and ascites samples were obtained from all patients. Serum samples from 5 cases of ovarian endometrioma and endometriosis-associated ovarian cancer each were submitted for comprehensive miRNA microarray profiling. We investigated the differential expression of miRNAs between the two groups to confirm the pivotal role of miRNAs. Quantitative reverse transcription-polymerase chain reaction validation of five selected miRNAs [miR-92a-3p, miR-486-5p, miR-4484, miR-6821-5p, and miR-7108-5p] was performed, and miR-486-5p expression analysis was followed by proliferation and wound healing assays, depending on the expression of miR-486-5p. Result miR-486-5p expression in serum and ascites samples from endometriosis-associated ovarian cancer patients was significantly higher than that from ovarian endometrioma patients. Moreover, the miR-486-5p level in serum and ascites samples was significantly correlated with the severity of the endometriosis. The upregulation of miR-486-5p in immortalized ovarian endometrioma cells significantly increased proliferation and migration. In contrast, the downregulation of miR-486-5p in these cells significantly decreased proliferation and migration. Conclusion miR-486-5p might function as an oncogenic miRNA in endometriosis-associated ovarian cancer and could be a noninvasive biomarker to prospect the severity of ovarian endometrioma.